Factors Influencing Pregnant Women's Compliance with Standard Pregnancy Examinations - Elvi Era Liesmayani; Nilda Tri Putri; Rima Semiarty; Vaulinne Basyir (GLOBAL HEALTH SCIENCE GROUP, 2025)
Antenatal care (ANC) refers to the care provided to mothers and their unborn babies during pregnancy. ANC visits are essential, as they allow for the early provision of important information and education regarding pregnancy and childbirth preparation. Objective to identify the factors influencing pregnant women's compliance with the minimum standard pregnancy examinations in the Deli Serdang District Health Office, North Sumatra. This study used a quantitative and cross-sectional approach, involving 138 pregnant using puposive sampling women from four community health centers under the Deli Serdang District Health Office, North Sumatra, Indonesia. Data were collected using questionnaires and analyzed using the McNemar, Chi-square, and multiple logistic regression tests The results of the study showed that factors influencing compliance with the minimum standard pregnancy examinations included the mother's last education level, gestational age, transportation, travel time, ANC visit frequency, media exposure, knowledge, and attitude, with a p-value of 0.000 < 0.05. The most dominant factor affecting compliance with ANC visits was the type of transportation used (p-value = 0.039). Education level, gestational age, transportation, travel time, ANC visit frequency, media exposure, knowledge, and attitude all influence compliance with ANC. Pregnant women should improve their attitude and motivation to seek information about healthy pregnancy using easier access, such as e-books or web links that can be read anytime and anywhere. In today's digital era, this can help increase awareness and knowledge about the importance of ANC, ultimately improving ANC coverage (K1-K4) and reducing maternal mortality rates.